2013
DOI: 10.1037/a0034006
|View full text |Cite
|
Sign up to set email alerts
|

Common dyadic coping is indirectly related to dietary and exercise adherence via patient and partner diabetes efficacy.

Abstract: Using cross-sectional data from 117 married couples in which one member is diagnosed with type 2 diabetes, the current study sought to explore a possible indirect association between common dyadic coping and dietary and exercise adherence via the mechanism of patient and spouse reports of diabetes efficacy. Results from the structural equation model analysis indicated common dyadic coping was associated with higher levels of diabetes efficacy for both patients and spouses which, in turn, was then associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 48 publications
3
65
0
Order By: Relevance
“…Likewise, researchers have highlighted the importance of considering age when examining chronic illness as older adults are more likely to have multiple chronic illnesses and increased likelihood of developing age-related chronic conditions (e.g., Roper & Yorgason, 2009). Finally, a longer time since diagnosis of Type 2 diabetes was found to be associated with lower patient diabetes self-efficacy (Johnson et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, researchers have highlighted the importance of considering age when examining chronic illness as older adults are more likely to have multiple chronic illnesses and increased likelihood of developing age-related chronic conditions (e.g., Roper & Yorgason, 2009). Finally, a longer time since diagnosis of Type 2 diabetes was found to be associated with lower patient diabetes self-efficacy (Johnson et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The link between diabetes self-efficacy and patient dietary and exercise adherence has also been found for spouses. Johnson et al (2013) used reports of both patient and spouse diabetes self-efficacy and found both were related to better patient dietary and exercise adherence. Our study extends the work of Johnson and colleagues by including multiple patient and spouse factors that could be related to patient dietary and exercise adherence through patient and spouse diabetes self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that patients with type 2 diabetes had better compliance with their diets. Compliance with diet is one of the self-care behaviors [49]. In another study, no significant correlation was observed between compliance with diet and self-care agency score [18].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of results was evident for spouse and patient emotional distress and diabetes efficacy. These findings underscore the buffering effect of intimate relationships for those with chronic illnesses and highlights how intimate unions may serve as a protective factor for diabetic individuals (Berg & Upchurch, ; Johnson et al, ). Our study also extends research on the dyadic experience of couples facing economic pressure (Conger et al, ; Masarik et al, ) by identifying a growing subpopulation of couples who may experience high levels of economic pressure due to the direct and indirect costs accrued from living with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 67%